2018
DOI: 10.7567/apex.11.111002
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of optically induced degradation in gallium nitride optoelectronic devices

Abstract: We provide experimental evidence that gallium-nitride-based optoelectronic devices can be affected by a photon-driven degradation mechanism unrelated to catastrophic optical damage. Any role of current in such degradation is excluded by stress tests under laser irradiation in the opencircuit configuration; any role of temperature is ruled out by additional thermal tests, showing a different degradation mode. Given the high bond strength of GaN, lattice-damage-related degradation is unlikely. A possible cause, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…De Santi et al investigated this topic on InGaN–GaN multiple quantum wells (MQWs) 1 × 1 mm 2 photodetectors, with 30 QWs. [ 109 ] These devices, that have a LED‐like structure, can be used in wireless power transfer systems and must be able to withstand optical intensities up to hundreds of W/cm 2 . The authors stressed the devices under open‐circuit conditions at 361 W cm −2 for 486 h with a 405 nm continuous wave laser diode.…”
Section: Degradation Processes Of Gan Ledsmentioning
confidence: 99%
See 3 more Smart Citations
“…De Santi et al investigated this topic on InGaN–GaN multiple quantum wells (MQWs) 1 × 1 mm 2 photodetectors, with 30 QWs. [ 109 ] These devices, that have a LED‐like structure, can be used in wireless power transfer systems and must be able to withstand optical intensities up to hundreds of W/cm 2 . The authors stressed the devices under open‐circuit conditions at 361 W cm −2 for 486 h with a 405 nm continuous wave laser diode.…”
Section: Degradation Processes Of Gan Ledsmentioning
confidence: 99%
“…De Santi et al investigated this topic on InGaN-GaN multiple quantum wells (MQWs) 1 Â 1 mm 2 photodetectors, with 30 QWs. [109] These devices, that have a LED-like structure, can be used in wireless power transfer systems and must be able to with the model proposed in the study by Ruschel et al [99] The devices under test were commercial UV-B LEDs with nominal current of 350 mA, stressed at 250 mA at room temperature for 300 h. Reproduced with permission. [24] Copyright 2020, The Optical Society.…”
Section: Optically Induced Degradationmentioning
confidence: 99%
See 2 more Smart Citations
“…d.) Photo-induced effects: Results presented by De Santi et al [62] demonstrated the formation of point defects in irradiated InGaN LEDs using a 405 nm laser and an irradiance of 361 W cm −2 . Similar results were reported by Caria et al [63] in open-circuit conditions.…”
Section: A Degradation Mechanismsmentioning
confidence: 99%